Cytologic and immunocytochemical characterization of feline progressive histiocytosis. (12th May 2014) - Pinto da Cunha, Nazaré; Ghisleni, Gabriele; Scarampella, Fabia; Fabbrini, Fabrizio; Sforna, Monica; Cornegliani, Luisa; Caniatti, Mario; Avallone, Giancarlo; Moore, Peter; Roccabianca, Paola
<x xml:space="preserve">Abstract</x> Background Feline Progressive Histiocytosis (FPH) is a cutaneous dendritic cell neoplasm characterized by slow progression and spread to internal organs in the terminal stage. FPH is often misdiagnosed as an inflammatory reaction and has not been fully characterized from a cytologic diagnostic perspective. Objectives The purpose of the study was to characterize the cytologic and immunocytochemical aspects useful for FPH diagnosis. Methods Fine‐needle aspiration cytologic samples of 5 cases of FPH confirmed by skin biopsy and necropsy were evaluated. Immunocytochemistry with antibodies recognizing CD1a, CD1c, CD3, CD11b, CD18, CD21, and MHCII was performed on air‐dried, acetone‐fixed smears. E‐cadherin expression was assessed on paraffin‐embedded skin biopsies. Transmission electron microscopy (TEM) was performed in one case. Results Main cytologic findings on variably cellular samples were characterized by single to cohesive large, round to polygonal cells with intermediate to low N/C ratio, abundant clear homogeneous cytoplasm, and round to oval nuclei with rare bi‐ to multinucleated atypical cells, associated with low numbers of small lymphocytes and/or neutrophils. Neoplastic cells expressed CD1a, CD1c, CD11b, CD18, and MHCII. Anti‐CD3 antibodies identified reactive T cells admixed with the neoplastic cells. E‐cadherin expression was observed in all but one case. TEM failed to identify Birbeck granules in one case. Conclusions FPH is a distinctive neoplastic lesion composed of nonphagocytizing histiocytes variably admixed with neutrophils and small mature lymphocytes. Immunocytochemical analysis with CD1 is mandatory to confirm a dendritic cell origin. Immunocytochemistry and cytomorphology allowed the specific and rapid diagnosis of FPH on cytologic samples.